Pathogenic Clones versus Environmentally Driven Population Increase: Analysis of an Epidemic of the Human Fungal Pathogen Coccidioides immitis - Fisher, Matthew C. (American Society for Microbiology, 2000)
For many pathogenic microbes that utilize mainly asexual modes of reproduction, it is unknown whether epidemics are due to either the emergence of pathogenic clones or environmentally determined increases in the population size of the organism. Descriptions of the genetic structures of epidemic populations, in conjunction with analyses of key environmental variables, are able to distinguish between these competing hypotheses. A major epidemic of coccidioidomycosis (etiologic agent, Coccidioides immitis) occurred between 1991 and 1994 in central California, representing an 11-fold increase above the mean number of cases reported from 1955 to 1990. Molecular analyses showed extensive genetic diversity, a lack of linkage disequilibria, and little phylogenetic structure, demonstrating that a newly pathogenic strain was not responsible for the observed epidemic. Epidemiological analyses showed that morbidity caused by C. immitis was best explained by the interaction between two variables, the lengths of droughts preceding epidemics and the amounts of rainfall. This shows that the principal factors governing this epidemic of C. immitis are environmental and not genetic. An important implication of this result is that the periodicity of cyclical environmental factors regulates the population size of C. immitis and is instrumental in determining the size of epidemics. This knowledge provides an important tool for predicting outbreaks of this pathogen, as well as a general framework that may be applied to determine the causes of epidemics of other fungal diseases.